Avaliação dos Projetos Proinf do Território Andradina (SP), a partir da perspectiva de diferentes atores - Tarsitano, Rodrigo Anselmo [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
A abordagem territorial das políticas públicas no Brasil é recente, iniciada em 2003 no âmbito da Secretaria de Desenvolvimento Territorial (SDT), do MDA. No Brasil foram criados 164 territórios, dos quais 5 no Estado de São Paulo e dentre estes o Território Rural Andradina. Este trabalho objetivou levantar e analisar os Projetos financiados nos municípios que compõem o Território Andradina com recursos do Proinf, entre os anos de 2004 e 2011. Neste período foi elaborado o Plano Territorial de Desenvolvimento Rural Sustentável do Território e aprovados 19 projetos para investimentos, somando quase dois milhões em recursos do Proinf. A grande maioria dos projetos manteve um caráter mais setorial, relacionado à pecuária leiteira, e com abrangência espacial limitada a um ou dois assentamentos rurais de um único município. Para que os projetos apresentados tenham maior abrangência territorial e institucional, e realmente contribuam para desenvolvimento territorial é necessário, além da ampliação dos recursos, uma maior articulação entre as instituições participantes

The territorial approach of public policy in Brazil is recent, initiated in 2003 in the ambit of the Clerkship of Territorial Development (SDT), of MDA. In Brazil, 164 territories were created, which 5 of them are located in the state of São Paulo and 1 of these 5 is the Rural Territory Andradina. This work aimed to analyze the financed Projects in the municipal districts that compose Andradina ́s territory with Proinf resources between 2004 and 2011. In this period, a Territorial Plan of Sustainable Rural Development was elaborated and 19 projects were approved for investments, totaling almost 2 million in Proinf resources. The majority of the projects maintained a more sectorial character and it is related to dairy cattle, spatial extend limited to one ore two rural settlements in a city. Besides resources increase, it was also considered important the greater coordination between participating institutions, so that the presented projects may have greater institutional and territorial coverage and really contribute to territorial development
Keywords: Desenvolvimento rural; Politicas publicas - Zona rural; Rural development; Public politics